Paradigma Transdisiplineritas dalam Pendidikan Islam - Sahaludin, Ah; Kurniawan, Iwan (Program Studi S3 Pascasarjana Universitas Islam Negeri Sultan Maulana Hasanuddin Banten, Indonesia, 2020)
This paper was written to explain the paradigm of trans-disciplinarity in Islamic education. Writing method using Microsoft Word and journal templates. Mendeley's application is used for citation and APA 7th (American Psychological Association 7th edition) as a reference style. The paper discussion data is obtained from primary and secondary data derived from books and journals of international and national reputable. The results of the paper show that trans-disciplinarity is a process characterized by the integration of various disciplines (multy-disciplines) of science to understand issues or problems and aims to build paradigms that can solve scientific problems across disciplines and different perspectives in undergoing the dynamics of civilization that continues to evolve; trans-disciplinary Islamic education orientation seeks to answer all challenges along with the times. paradigmatic analysis of transdisciplinary Islamic education in the framework of the development of superior human resources and character must accentuate the spiritual integrity that colors the dynamics of the development of various scientific disciplines, based on the rules; trans-disciplinary Islamic education curriculum development must be developed holistically in order to develop existing potentials.